Boundaries of National Belonging in Ingrian Finnish Return Migration: 'A Multi-level Perspective' - Tuuli Anna Mähönen; Sirkku Varjonen; Nicholas Prindiville; Linda Arnold; Inga Jasinskaja-Lahti (Nordic Journal of Migration Research, 2015)
This study examines the discursive construction of Finnishness within the context of Ingrian Finns’ return migration from Russia to Finland. The focus is on how characteristics of Finnishness, especially ancestry and language, are employed at institutional, community and interpersonal levels of text and talk. The results show how the same characteristics can be used to both in- and exclude Ingrian Finns from the national ingroup, and how essentialist notions of ethnonational belonging can be used strategically by both state authorities and Ingrian Finns themselves to make claims about their Finnishness and right to remigrate.